Korelasi Indeks Massa Tubuh dengan Indeks Aterogenik Plasma pada Penyandang Obes - M Hasbi Siddiq Eel Taslim (Fakultas Kedokteran, Universitas Andalas, 2026)
Abstract Background: Obesity is a state of excess fat accumulation in the body and cardiovascular disease major risk factor. Body mass index is a simple way of measuring adult nutritional status that indirectly measures the estimated total body fat mass. Atherogenic index of plasma was calculated as logarithmic 10 ratio of triglyceride-high density lipoprotein [log10 (TG/HDL)]. Atherogenic index of plasma is a marker of atherogenicity associated with risk or predictors of cardiovascular disease Objective: This study aims to know the correlation between body mass index and atherogenic index of plasma in obese people Methods: This study Objective to know the correlation between body mass index and atherogenic index of plasma in obese people. An analitycal observational study was done using cross sectional approach by using laboratory data in RSUP Dr. M. Djamil Padang. The sample consist of 30 obese people aged 25 to 57 years, period from May-December 2019. Univariate and bivariate data were analyzed using Pearson correlation test with p <0.05 is considered statistically significant. Result: The results of this studys with univariate analysis are shows the average of subjects is 36.8+9.19 years, the average of BMI 27.09±1,27 kg / m2, and AIP 0.42±0.25. Bivariate analysis found there was significantly medium positive correlation between BMI and AIP (r = 0.476; p = 0.008). Conclusion: This study concludes that there is a correlation between BMI and AIP in obese people.